Taking Trade-offs Seriously: Examining the Contextually Contingent Relationship Between Social Outreach Intensity and Financial Sustainability in Global Microfinance - Wry, Tyler; Zhao, Eric Yanfei (Organization Science, 2018)
A key insight from research on hybrid organizing is that the joint pursuit of competing goals exposes an enterprise to potentially problematic tensions and trade-offs. Yet while studies have examined the former, the actual trade-offs that these organizations face—and how these might vary among enterprises and contexts—has been largely overlooked. Focusing on social enterprise, we address these gaps by (1) developing a framework that can be used to predict the compatibility of social outreach and financial sustainability for different types of enterprises and (2) arguing that the acuteness of trade-offs will vary based on the cultural roots of the issue an enterprise addresses, the market conditions where it operates, and the quality of its management. We test our arguments by studying 2,037 microfinance organizations in 115 nations between 1995 and 2013. Results support our predictions. Social–financial trade-offs are amplified when a social issue is intertwined with deep-seated cultural problems, such as discrimination, and when an enterprise operates in a weak institutional environment. Intensive social outreach becomes sustainable, however, when cultural barriers to outreach are low, market-supporting institutions are strong, and an enterprise is professionally managed. Our study thus shows that social–financial trade-offs are contingent and that the promise of sustainable social outreach varies widely across contexts. The e-companion is available at https://doi.org/10.1287/orsc.2017.1188 .